PKM Pemberdayaan Kelompok Nelayan di Desa Galesong Kota Kabupaten Takalar sebagai Upaya Peningkatan Ekonomi dan Keselamatan Kerja - Alwi, Muhammad Rusydi; Shintarahayu, Balqis; Clausthaldi, Fadhil Rizki; Fajar, Muhammad; Alfira, Alfira (Faculty of Engineering UNHAS, 2023)
Galesong Kota is one of the villages in Galesong District, Takalar Regency. Residents in Galesong Kota Village mostly work as fishermen, every day looking for fish across the sea for their survival. The community implements a capture fisheries system. One of the traditional capture fisheries businesses in Galesong Kota Village is called